2020
DOI: 10.1073/pnas.2013244117
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected specificity within dynamic transcriptional protein–protein complexes

Abstract: A key functional event in eukaryotic gene activation is the formation of dynamic protein–protein interaction networks between transcriptional activators and transcriptional coactivators. Seemingly incongruent with the tight regulation of transcription, many biochemical and biophysical studies suggest that activators use nonspecific hydrophobic and/or electrostatic interactions to bind to coactivators, with few if any specific contacts. Here a mechanistic dissection of a set of representative dynamic activator•… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 59 publications
2
56
0
Order By: Relevance
“…Protein-protein interactions between transcriptional activators and coactivators play a critical role in gene expression. [49][50][51] From the established PE Wright' structural model for the KIX-MLL complex and this study, we found that the residues in p3 and p4 positions of the first 9aaTAD region (p1-4) and the KIX α1-α2-α3 region consisted of I611, L628, and I660 are responsible for conformation changes in the flexible hydrophobic groove in KIX L12-G2 region. The residues in p6 and p7 positions of the second 9aaTAD region (p6-9) provided second hydrophobic interaction necessary for high-affinity binding.…”
Section: Simplified Hydrophobic Residues Patterns φXxφφ and φφXxφ For Kix Bindingmentioning
confidence: 62%
“…Protein-protein interactions between transcriptional activators and coactivators play a critical role in gene expression. [49][50][51] From the established PE Wright' structural model for the KIX-MLL complex and this study, we found that the residues in p3 and p4 positions of the first 9aaTAD region (p1-4) and the KIX α1-α2-α3 region consisted of I611, L628, and I660 are responsible for conformation changes in the flexible hydrophobic groove in KIX L12-G2 region. The residues in p6 and p7 positions of the second 9aaTAD region (p6-9) provided second hydrophobic interaction necessary for high-affinity binding.…”
Section: Simplified Hydrophobic Residues Patterns φXxφφ and φφXxφ For Kix Bindingmentioning
confidence: 62%
“… 36 Therefore, a mechanistic understanding of dynamic protein complexes with refined methods as well as the role of privileged conformations and populations could provide untapped opportunities in protein degradation workflows. 37 , 38 …”
Section: Induced Cooperativity and Pursuit Of Privileged Ternary Complexes For Proteasomal Degradationmentioning
confidence: 99%
“… 34 , 48 Complementary to measuring k off / k on rates and dissociation half-lives, native mass spectrometry can provide additional granularity of ternary complex formation and intermediate conformational states in a single label-free experiment. 49 Future approaches to further explore degradation opportunities may require an in-depth kinetic analysis of protein complexes as those used for dynamic transcription factors, 37 which microfluidics and single molecule studies may also be well positioned to address. 50 Drawing from enzymology principles, a deeper appreciation and mechanistic understanding of energetics for protein ensembles could provide new avenues for protein degradation paradigms.…”
Section: Induced Cooperativity and Pursuit Of Privileged Ternary Complexes For Proteasomal Degradationmentioning
confidence: 99%
“…The domain of Med25 that interacts with activators is the Activator-Interaction Domain (AcID) (Figure 1A). 19,[22][23][24][25][26][27][28] This domain contains a 7-stranded beta barrel core flanked with dynamic loops and three alpha helices. Like other activator-binding domains (ABDs) within coactivators, AcID does not contain defined binding pockets, but rather relies on hydrophobic interfaces, termed H1 and H2, to interact with transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…17,29 Recently, we reported that the dynamic substructures within AcID contain allosteric hotspots that regulate cooperativity and selectivity in binding. 20,28 Thus, we hypothesized that these substructures, largely loop regions, represent an opportunity for allosteric inhibition. Further, because such substructures are more likely to access conformations with topologically unique binding surfaces, one might anticipate that small-molecule modulators of such sites would exhibit enhanced selectivity compared to purely orthosteric ligands.…”
Section: Introductionmentioning
confidence: 99%